Upaya Penanganan Hipertensi Stage 1 Pada Pasien Perempuan Usia 38 Tahun Melalui Pendekatan Kedokteran Keluarga Di Puskesmas Nisam Kabupaten Aceh Utara - Aida Fitri Harahap; Noviana Zara (Journal of Medical Practice and Research, 2026)
This study aimed to analyze the implementation of a family medicine approach in managing stage 1 hypertension in a 38-year-old female patient at a primary healthcare facility. The research employed an empirical case report design with a qualitative descriptive approach, integrating clinical assessment, behavioral evaluation, and family-based analysis. Data were collected through in-depth anamnesis, physical examination, home visits, and the use of family medicine instruments, including genogram, APGAR, and SCREEM. The findings demonstrated that comprehensive management combining pharmacological therapy, lifestyle modification, and family involvement contributed to improved blood pressure control and enhanced patient adherence. Behavioral changes were observed in dietary patterns, physical activity, and stress management, supported by strengthened family support systems. The integration of patient-centered care and contextual family assessment enabled more sustainable health outcomes compared to conventional approaches. These results highlight the importance of holistic, continuous, and family-oriented care in managing hypertension at the primary care level, particularly among productive-age patients with modifiable risk factors and complex psychosocial backgrounds.